PENGARUH STRUKTUR MODAL, KESEMPATAN INVESTASI SERTA KEBIJAKAN KEUANGAN TERHADAP RISIKO DAN KINERJA KEUANGAN PADA BUMN YANG DIPRIVATISASI MELALUI PASAR MODAL INDONESIA - Agus Buniarto, Edwin (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2008)
The aims of this study is to examine the change of Financial Performance of state own companies after going public in Indonesian capital market.This studi used data from financial statement of the state own companies, This study also used thirteen companies as sample. Field research was applied, data collection uses documentation technique.There is one statistical analysis used in this study, that isPartial Least Square(PLS).Parcial Least Squareis used to analyse five variables, those are Investment Opportunity Set (IOS), Financial Policy, Capital Structure, Risk and Financial Performance.The result of this study found that, Investment Opportunity Set influence Risk during 1998-2005. The result also show that Capital Structure do not influence Financial Performance. But, Financial Policy is significance influencing Financial Performance. Finally, the result of the study indicate that financial policy influence Financial Performance of company.Â Key words : Capital Structure, Investment Opportunity Set, Financial Policy, Risk and Financial Performance.